Model for predicting the shear strength and strains of thin concrete panels retrofitted with CFRP. (November 2022) - Carrillo, Julian; Rodriguez, Daniela; Takeuchi, Caori
Abstract: Carbon Fiber Reinforced Polymers (CFRP) can be an alternative material to retrofit thin and low-rise concrete walls. The literature review reports no predictive backbone models that include the deformation associated with the main limit states of concrete panels retrofitted with CFRP fabrics. This paper aims to describe a backbone model to predict the shear strength and strains associated with the peak shear strength ( max ) and the loss of lateral resistance ( llr ) limit states of thin concrete panels retrofitted with CFRP strips. A model to correlate the shear strength associated with the max and llr limit states between panels and walls was developed to extrapolate the response from panels to walls. The experimental program includes cyclic diagonal compression tests of 15 panels. The results obtained allowed analyzing the hysteresis curves, the shear strengths and strains, and the energy dissipation associated with the max and llr limit states in the panels. The response of specimens retrofitted with CFRP were compared with those retrofitted with conventional methods, and with specimens that comply the minimum web shear steel ratio. The response measured in the panels showed that the dissipated energy associated with the limit states depends on the volumetric ratio, the inclination, and the number of CFRP strips. Results also demonstrate that performance of panels retrofitted with CFRP strips outperforms that of panels with the minimum web shear steel ratio.